2022
DOI: 10.3389/fpls.2021.716011
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Live-Imaging Analysis for Polarized Growth of Conchocelis in the Multicellular Red Alga Neopyropia yezoensis

Abstract: A wide range of tip-growing cells in plants display polarized cell growth, which is an essential cellular process for the form and function of individual cells. Understanding of the regulatory mechanisms underlying tip growth in terrestrial plants has improved. Cellular processes involved in tip growth have also been investigated in some algae species that form filamentous cells, but their regulatory mechanisms remain unclear. In the macro red alga Neopyropia yezoensis, for which genome information has recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Despite the successful establishment of industrial large-scale aquaculture systems for N. yezoensis at the sea surface, our biological understanding of this alga is limited, and the regulatory mechanisms of its growth, life cycle, development, and environmental stress responses are mostly unknown. We recently demonstrated that tip growth is essential for maintaining the proliferation of the filamentous generations of N. yezoensis , including the conchocelis (sporophyte generation) and conchosporangium (conchosporophyte generation) [ 39 , 40 , 41 , 42 ]. In these generations, only the apical tip cell undergoes elongation and division, which results in the production of two different cell types: a copy of the apical cell at the tip of the filament and a neighboring differentiated nondividing cell [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the successful establishment of industrial large-scale aquaculture systems for N. yezoensis at the sea surface, our biological understanding of this alga is limited, and the regulatory mechanisms of its growth, life cycle, development, and environmental stress responses are mostly unknown. We recently demonstrated that tip growth is essential for maintaining the proliferation of the filamentous generations of N. yezoensis , including the conchocelis (sporophyte generation) and conchosporangium (conchosporophyte generation) [ 39 , 40 , 41 , 42 ]. In these generations, only the apical tip cell undergoes elongation and division, which results in the production of two different cell types: a copy of the apical cell at the tip of the filament and a neighboring differentiated nondividing cell [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated that tip growth is essential for maintaining the proliferation of the filamentous generations of N. yezoensis , including the conchocelis (sporophyte generation) and conchosporangium (conchosporophyte generation) [ 39 , 40 , 41 , 42 ]. In these generations, only the apical tip cell undergoes elongation and division, which results in the production of two different cell types: a copy of the apical cell at the tip of the filament and a neighboring differentiated nondividing cell [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%